2016
DOI: 10.1021/acsami.6b00512
|View full text |Cite
|
Sign up to set email alerts
|

High-Performance Protonic Ceramic Fuel Cells with Thin-Film Yttrium-Doped Barium Cerate–Zirconate Electrolytes on Compositionally Gradient Anodes

Abstract: In this study, we used a compositionally gradient anode functional layer (AFL) consisting of Ni-BaCe(0.5)Zr(0.35)Y(0.15)O(3-δ) (BCZY) with increasing BCZY contents toward the electrolyte-anode interface for high-performance protonic ceramic fuel cells. It is identified that conventional homogeneous AFLs fail to stably accommodate a thin film of BCZY electrolyte. In contrast, a dense 2 μm thick BCZY electrolyte was successfully deposited onto the proposed gradient AFL with improved adhesion. A fuel cell contain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(25 citation statements)
references
References 39 publications
0
21
0
Order By: Relevance
“…Another factor that can affect the performance of the cell is the low sintering temperature (1200 °C), which results in a small TPB length, therefore causing a reduced electrochemical reaction at the TPB [25,36,48]. In the present case, the power density of 390 mW cm −2 at 600 °C for BaCe0.7-xSmxZr0.2Y0.1O3-δ sintered at a low sintering temperature is better than the 300 (mWcm −2 ) at 550 °C for BaCe0.5Zr0.35Y0.15O3-δ, which can be improvedby sintering material at a high temperature [49].…”
Section: Electrochemical Performancementioning
confidence: 57%
“…Another factor that can affect the performance of the cell is the low sintering temperature (1200 °C), which results in a small TPB length, therefore causing a reduced electrochemical reaction at the TPB [25,36,48]. In the present case, the power density of 390 mW cm −2 at 600 °C for BaCe0.7-xSmxZr0.2Y0.1O3-δ sintered at a low sintering temperature is better than the 300 (mWcm −2 ) at 550 °C for BaCe0.5Zr0.35Y0.15O3-δ, which can be improvedby sintering material at a high temperature [49].…”
Section: Electrochemical Performancementioning
confidence: 57%
“…BaCeO 3 , in contrast, exhibits higher proton conductivity; however, its stability is relatively poor because of its decomposition into CeO 2 and BaCO 3 in CO 2 environment . Compositional proton‐conducting electrolyte with BaZrO 3 and BaCeO 3 has been recently introduced to enhance the performance of proton conducting fuel cells (PCFCs) operating at low temperatures . Recent reports by Ha and Li demonstrated the use of dense thin film yttria‐doped barium zirconate (BYZ, BaZr 0.8 Y 0.2 O 3−δ ) electrolyted by pulse laser deposition (PLD) technique for thin‐film SOFCs (Figures (c) and 6(d)).…”
Section: Membrane Designs and Materialsmentioning
confidence: 99%
“…In barium or strontium cerates, rare earth elements such as Yb, Gd, Nd, and Y are the most common dopants due to their ionic radii size closeness to cerium or zirconium [2]. In various studies [3][4][5], these cerates have shown a relatively high protonic conductivity, but also react in acidic environments to form carbonates in environments with CO 2 and H 2 O. Zirconates are more chemically stable and have better mechanical properties, react poorly in acidic environments, are stable in a CO 2 environment, but have a significantly lower proton conductivity [6,7]. Different approaches were made to find the best combination of a high protonic conductivity and a high chemical and mechanical stability, such as the modifications of technological parameters or the incorporation of the different dopant concentrations [4,8,9].…”
Section: Introductionmentioning
confidence: 99%